The Theory of Practice and the Development of Ambidexterity in Software Innovation Process - Adriano Olímpio Tonelli; André Luiz Zambalde; Mozar José de Brito; Paulo Henrique de Souza Bermejo (BBR: Brazilian Business Review)
This study aims to point out and analyze, from the perspective of practice theory, the process in which ambidexterity are formed within the innovation process, considering the mutual constitution between local actions and institutional logics. Qualitative data were collected from a longitudinal approach throughout the development of an innovative software solution for the mining industry. The results show that process of becoming ambidextrous is based on three stages that reflect the relationships between logics and actions: generation of initial conflicts, reaction to conflicts and stabilization via logic-action dynamics.